KEPEMIMPINAN DALAM MEMBENTUK BUDAYA KERJA DI SEKRETARIAT JENDERAL KEMENTERIAN LINGKUNGAN HIDUP DAN KEHUTANAN - Hakanna, Hakanna; Iskandar, Abubakar; Sudarsa, Agus Suarman (Administratie: Jurnal Administrasi Publik, 2021)
The Ministry of Environment and Forestry is innovative, the consequence is to have new ideas that are not yet known by the general public. Innovation is defined as a new method to improve the quality and quantity of a product and this is the focus of attention and improve its performance in the latest way. In a situation like this, a leader's role is needed in shaping his work culture. The objectives of the research are: To explain that transformational leadership styles can improve employee education; Analyzing transformational leadership styles can involve employees in skills training; Knowing the transformational leadership style implementing new ideas; Describe the transformational leadership style involving employees in various trainings. The research design is cross sectional using quantitative analysis. The population is all employees, while the sample is 30 people. Data was collected through questionnaires, and asked the respondents to answer them. Data were analyzed through dummy regression. The results showed that the correlation coefficient value was 0.731, meaning that it was very strong. The correlation coefficient value was 0.485, indicating that the relationship was not strong. The correlation coefficient value of 0.688 indicates that the relationship is not strong. The correlation coefficient value of 0.499 indicates a not strong relationship.